2022
DOI: 10.1016/j.ultsonch.2021.105871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity ultrasound on the physicochemical properties, microstructure, and stability of soy protein isolate-pectin emulsion

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 40 publications
(40 reference statements)
4
40
0
Order By: Relevance
“…However, with the increase of ultrasound power, the absolute ζ-potential of the sample began to decrease gradually. This was similar to the finding of Wang et al [ 23 ]. The particle size of the emulsion decreased as the cavitation effect and high shear force provided by HIU treatment.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, with the increase of ultrasound power, the absolute ζ-potential of the sample began to decrease gradually. This was similar to the finding of Wang et al [ 23 ]. The particle size of the emulsion decreased as the cavitation effect and high shear force provided by HIU treatment.…”
Section: Resultssupporting
confidence: 93%
“…This was owing to the cavitation effect and physical shear force generated by ultrasonic treatment that broke the oil droplets of emulsion into small particles, and then the particle size of emulsion turned to be smaller, this could improve the emulsification of emulsion [ 22 ]. Data in the research showed the emulsifying properties of emulsions began to decrease slightly at 450 W and 600 W. This was because excessive ultrasound power can affect the interfacial protein structure, leading to flocculation of interfacial proteins and aggregation of emulsion droplets, thus reducing the emulsifying properties of the emulsion [ 23 ]. Overall, HIU treatment improved the emulsifying properties of emulsion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that HSO (red) is covered by HPI (green), and the HIU treatment increases the dispersibility of the emulsion and avoids aggregation of the emulsion compared to the emulsion without HIU treatment. The smallest particle size of the emulsion was observed at a HIU power of 450 W, a phenomenon that remained consistent with our previous study [20] . The particle size reduction is probably caused by the cavitation force generated by the microflow of the ultrasonically treated probe.…”
Section: Resultssupporting
confidence: 92%
“…Taha et al [19] investigated ultrasonic-assisted emulsions stabilized with different plant and animal proteins and found that ultrasonic treatment increased the interfacial protein content and thermal stability. Wang et al [20] has studied the effect of different HIU powers on soybean isolate protein-pectin emulsions and the its stability was highest at 450 W. HIU has been considered as a green, safe and efficient method to assist in the preparation of emulsions.…”
Section: Introductionmentioning
confidence: 99%